Developing a knowledge management approach for an agricultural innovation system: the case of the Southern African Bean Research Network (SABRN) - Muthoni Andriatsitohaina, Rachel; Staiger Rivas, Simone; Beelen, Koen; Bheenick, Krishan (2017)
This paper is a case study of a network that combined participatory approaches to propose best suited knowledge management (KM) interventions for its member countries. A five-step exercise used existing elements of the alliance’s strategy, a KM survey and a face-to-face participatory validation of the analysis, to identify gaps in current KM approaches and to collectively point to immediate opportunities for improvement. The KM survey, also referred to as a scan, provided a neutral space for reflection. Its conclusions through the workshop process were crucial in confirming the network's strengths and weaknesses specific to KM. Feeding back the results into existing work plans provided concrete opportunities for country members to implement ideas that had been discussed. The approach to and the outputs of this exercise were extrapolated to formulate a theory of change on KM for the alliance.